PERAN CITRA DESTINASI MEMEDIASI PENGARUH E-WOM TERHADAP NIAT BERKUNJUNG KEMBALI WISATAWAN (Studi Pada Obyek Wisata Taman Edelweis Bali) - Utama, I Putu Hari Budi; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen; Vol 9 No 4 (2020)DO - 10.24843/EJMUNUD.2020.v09.i04.p01, 2020)
This study aims to explain the role of destination image in mediating the effect of e-WOM on the intention to revisit tourists in Bali's Edelweis Park. The number of samples taken was 128 domestic tourists who had visited the Bali’s Edelweis Park tourism object with a purposive sampling method that had criteria as Indonesian citizens, aged 17 years and over, and had visited the Bali’s Edelweis Park tourism object. Data was collected through questionnaires. The analysis technique used is Path analysis and Sobel test. The results of this study indicate that the e-WOM variable has a positive and significant effect on the intention of revisit tourists. Then e-WOM variable has positive and significant effect on destination image, and destination image variable has positive and significant effect on tourist revisit intention. In addition, the destination image variable also partially mediates the effect of e-WOM on the intention of revisit tourists. Keywords: e-WOM, destination image, and intention to revisit tourist